2021
DOI: 10.12659/ajcr.931702
|View full text |Cite
|
Sign up to set email alerts
|

A Severe Case of Diabetic Ketoacidosis and New-Onset Type 1 Diabetes Mellitus Associated with Anti-Glutamic Acid Decarboxylase Antibodies Following Immunotherapy with Pembrolizumab

Abstract: Patient: Female, 51-year-old Final Diagnosis: Diabetic ketoacidosis Symptoms: Abdominal pain • diarrhea Medication: Pembrolizumab Clinical Procedure: — Specialty: Endocrinology and Metabolic Objective: Unusual or unexpected effect of treatment Background: Immune checkpoint inhibitors (ICIs) are a novel class of antibodies, which have been increasingly utilized in cancer immunotherapies. Pembrolizuma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Due to the rapid onset of DM, patients with ICI-DM may test positive for diabetes autoantibodies. Of note, this differs from conventional T1DM (51).…”
Section: Discussionmentioning
confidence: 81%
“…Due to the rapid onset of DM, patients with ICI-DM may test positive for diabetes autoantibodies. Of note, this differs from conventional T1DM (51).…”
Section: Discussionmentioning
confidence: 81%
“…Baseline characteristics are presented in Table 2 . In addition to our patients, 171 cases were identified [ 7 , 8 , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [...…”
Section: Resultsunclassified
“…Lo Preiato et al [22] agreed that a total of 43.0% of patients had positive anti-GAD antibodies in their database, in contrast with the much higher prevalence of type 1 DM, with no comparison with a control group. Many reports have identified CPI-DM cases with both positive and negative specific autoantibodies but without strong conclusions [23][24][25][26]. A case report and literature review study showed that islet autoantibodies may be present before CPI treatment in non-diabetic patients and, when exposed to CPI therapy, may precipitate the onset of DM [27].…”
Section: Discussionmentioning
confidence: 99%
“…A case report and literature review study showed that islet autoantibodies may be present before CPI treatment in non-diabetic patients and, when exposed to CPI therapy, may precipitate the onset of DM [27]. Positive autoantibodies were associated with earlier and more severe presentations of CPI-DM [23][24][25][26]. In our series, positive islet autoantibodies were detected in three of four cases (one with anti-IA2, one with anti-GAD positivity, and one with anti-IA2, anti-GAD, and anti-ZnT8 positivity).…”
Section: Discussionmentioning
confidence: 99%